(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
The analysis of potential hydrological changes and nutrient loading in the basin of the Cheboksary Reservoir in the 21st century is based on future climate projections derived from an ensemble of Coupled Model Intercomparison Project Phase 6 (CMIP6) General Circulation Models (GCMs). These models were selected according to their reliability in reproducing regional climate patterns under two climate change scenarios. The study evaluates the coefficient of variation in annual runoff and the runoff of low-water years with 95% exceedance probability, as well as the total precipitation during the cold season in the Cheboksary Reservoir basin. An approximate assessment of the total nitrogen (Ntot) and total phosphorus (Ptot) loading on the Cheboksary Reservoir was conducted using mathematical modeling based on available observational data from pilot watersheds and projected for the 21st century using data from one GCM.